2004
DOI: 10.1001/archotol.130.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Administration of Ropivacaine With Epinephrine on Postoperative Pediatric Adenotonsillectomy Recovery

Abstract: To determine whether perioperative administration of ropivacaine hydrochloride with epinephrine decreases postoperative pain following adenotonsillectomy and to determine the pharmacokinetics of ropivacaine following injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…Similar studies investigating other types of surgery, including tonsilletomy 19 , orchidopexy 13 , hypospadias repair 3 , appendicectomy 25 and femoral nailing 10 , have demonstrated significant reductions in postoperative pain with the use of intraoperative local anaesthesia. Interestingly, in another study when ropivacaine with epinephrine was administered immediately after tonsillectomy the authors were unable to demonstrate any reduction in postoperative pain 20 .…”
Section: Discussionmentioning
confidence: 91%
“…Similar studies investigating other types of surgery, including tonsilletomy 19 , orchidopexy 13 , hypospadias repair 3 , appendicectomy 25 and femoral nailing 10 , have demonstrated significant reductions in postoperative pain with the use of intraoperative local anaesthesia. Interestingly, in another study when ropivacaine with epinephrine was administered immediately after tonsillectomy the authors were unable to demonstrate any reduction in postoperative pain 20 .…”
Section: Discussionmentioning
confidence: 91%
“…So, it appears that there is no synergistic or even additive effect in pre-operative infiltration of bupivacaine and pethidine and it is not a very effective method to control post-tonsillectomy pain. Published data regarding the analgesic effect of local anaesthetic infiltration into the peritonsillar tissue is equivocal and several studies showed that if there is any role, it is limited to the immediate postoperative period [8][9][10][11][12][13]. Hollis et al [14] reviewing six randomised controlled trials, concluded that there is no evidence that the use of peri-operative local anaesthetic in patients undergoing tonsillectomy improves postoperative pain control.…”
Section: Discussionmentioning
confidence: 99%
“…And they also observed that lower pain scores persisted until the fifth postoperative day only with clonidine containing ropivacaine infiltration. In contrast to previous study Park et al found no significant difference between placebo and ropivacaine infiltration in paediatric tonsillectomy operations in terms of postoperative pain scores and adverse effects [17]. However, these results are contributed to low dose ropivacine and the authors concluded that, 30 mg 0.5% ropivacaine is insufficient for providing adequate postoperative analgesia.…”
Section: Discussionmentioning
confidence: 64%